2018
DOI: 10.1002/ijop.12472
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and perceptions of organisational justice

Abstract: This study examined the association between five-factor model personality traits and perceptions of organisational justice. The sample for the study comprised 903 participants (35-50 years old; 523 women) studied in 2007 and 2012. Measures used were the Neuroticism, Extraversion, Openness, Five-Factor Inventory questionnaire and the short organisational justice measure. The results showed that high neuroticism was associated with low distributive, procedural and interactional justice. Furthermore, high agreeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
(78 reference statements)
1
16
0
2
Order By: Relevance
“…Because of t-count (3.499)>t-table (1.971), it is the significant path coefficient, it proves that there is a significant direct influence of Personality towards organization justice of employee's education office in Jakarta. The result of the study related to other research, that personality connected with perceptions of organizational justice, towards sample consisted of 903 participants [40]. Compare with our research that their research had a larger sample, so it will be more accurate in supporting our result research.…”
Section: Research Question 5: Whether There Is a Direct Influence Of Personality On Organizational Justice?supporting
confidence: 76%
“…Because of t-count (3.499)>t-table (1.971), it is the significant path coefficient, it proves that there is a significant direct influence of Personality towards organization justice of employee's education office in Jakarta. The result of the study related to other research, that personality connected with perceptions of organizational justice, towards sample consisted of 903 participants [40]. Compare with our research that their research had a larger sample, so it will be more accurate in supporting our result research.…”
Section: Research Question 5: Whether There Is a Direct Influence Of Personality On Organizational Justice?supporting
confidence: 76%
“…31 For example, Törnroos et al (2019) found that agreeableness relates positively to procedural and interactional justice. 29 Given the fact that there exist great within-culture individual differences in respecting and practicing the renqing norm, 25,32 we believe that followers agreeableness serves as a moderator in the relationship linking two components of perceptions of renqing and overall justice. In particular, we argue that when perceiving a high level of perceptions of renqing at the workplace, agreeable employees may be more prone to stronger justice perceptions through their high sensitivity to the interpersonal interactions (ie, affective interaction) and managerial practices (discretionary consideration) characterized by helping, caring for others, showing sympathy, and flexibility.…”
Section: The Moderating Role Of Followers Trait Agreeablenessmentioning
confidence: 99%
“…In addition, prior studies verified the significant association between employees’ organizational justice perceptions and five-factor model personality traits; among them, agreeableness is one critical factor. 29 Agreeableness is characterized by trust in and sympathy towards others. 30 Agreeable individuals are more likely to be high in prosocial and functional tendencies (eg, conducting more OCB) due to their high interpersonal sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies considering more traditional personality predictors have shown that Conscientiousness, Agreeableness, and Emotional stability are strong predictors of counterproductive work behaviors (Berry et al, 2007;Dalal, 2005). Further, referring to justice perceptions influenced by characteristics of the perceiver, personality traits such as Extraversion, Neuroticism, Agreeableness, and Openness have been associated with organizational justice (Barsky & Kaplan, 2007;Törnroos et al, 2019).…”
Section: The Incremental Validity Of Equity Sensitivity Over the Big Five Modelmentioning
confidence: 99%
“…It represents people's tolerance for underreward or over-reward in their transactions with the organization and relevant others (King, Miles, & Day, 1993). This individual difference has been studied in association with various attitudes and behaviors at work dimensions of personality from the Five-Factor Model (Bing & Burroughs, 2001;Scott & Colquitt, 2007) and Big Five traits also predict counterproductive work behaviors and perceived organizational justice (Berry, Ones, & Sackett, 2007;Törnroos et al, 2019). Because it was suggested that this construct may be a central factor in the workplace (i.e., related to important work outcomes; Miles et al, 1989;Grant, 2013), these statements should be supported by data, being crucial to establish whether equity sensitivity can be considered a valid predictor of organizational outcomes.…”
Section: Introductionmentioning
confidence: 99%